Legal and Problematic Protection of Social Movements to The Tau Taa Wana Indigenous People - Muhammad Hatta Roma Tampubolon (Susbtantive Justice International Journal of Law, 2020)
Social movements of the legal community of Tau Taa Wana Custom is a struggle to release threats and structural shackles and want recognition of customary (communal) rights that they deserve. This study aims to analyze and explain the factors that led to the birth of the Tau Taa Wana indigenous peoples' social movements. The research design is descriptive qualitative with a case study approach. Research informants as many as 5 people selected purposively. Data collected through observation, in-depth interviews and literature study. the results showed that the social movement of the Tau Taa Wana indigenous people was driven by three determinants namely, the threat of capitalist expansion through an expansion of oil palm plantations, the threat of loss of communal natural resources due to oil palm expansion, the creation of solidarity in maintaining customary rights and local wisdom. It was concluded that Tau Taa Wana customary law community social movements are caused by policy imbalances, weak state protection functions and the lack of state recognition of the existence of Tau Taa Wana indigenous peoples